FCγII (CD32) MONOSIT DI INFEKSI DENGUE PRIMER DAN SEKUNDER {FcγRII (CD32) Monocytes in Primary and Secondary Dengue Infection} - Umi S. Intansari; Usi Sukorini; Shanti Ika Sari (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Dengue infection is a major health problem in the world, including Indonesia. Clinical manifestations of dengue infection varywidely, from asymptomatic until dengue shock syndrome (DSS). Antibody Dependent Enhancement (ADE) hypothesis that states thatnon-neutralizing antibodies in secondary dengue infection may enhance dengue infection via Fcγ receptors is still controversial. Clinicalresearch shows that not all secondary infections manifest as DHF/DSS, but nearly all DHF/DSS cases are caused by secondary infection.Allegedly, the expression of Fcγ has an effect on this incident. This study is an observational analytical study with a cross sectional designto determine the expression of FcγRII (CD32) monocytes in patients with primary and secondary dengue infection. CD32 of monocyteswas measured using FACS Calibur with lyse no wash technique. Primary and secondary dengue infection were determined by IgM/IgGoptical density ratio using ELISA capture method. The ratio of IgM/IgG ≥1.2 was considered as primary infection, while the ratio <1.2was considered as secondary infection. Twenty primary and 32 secondary dengue infection patients in acute phase of dengue infectionpartisipated in this study. Expressions of Fcγ RII (CD32) monocytes were significantly lower in primary than secondary dengue infection(187.825±31.584 vs 218.598±43.414 MFI; p=0.008). CD32 expressions were higher in day 3 compared to day 4 of fever.